Configuration and Validation of an Oceanic Physical and Biogeochemical Model to Investigate Coastal Eutrophication in the Southern California Bight. (1st December 2021) - Kessouri, Fayçal; McLaughlin, Karen; Sutula, Martha; Bianchi, Daniele; Ho, Minna; McWilliams, James C.; Renault, Lionel; Molemaker, Jeroen; Deutsch, Curtis; Leinweber, Anita
Abstract: The Southern California Bight (SCB), an eastern boundary upwelling system, is impacted by global warming, acidification, and oxygen loss and receives anthropogenic nutrients from a coastal population of 20 million people. We describe the configuration, forcing, and validation of a realistic, submesoscale‐resolving ocean model as a tool to investigate coastal eutrophication. This modeling system represents an important achievement because it strikes a balance of capturing the forcing by U.S. Pacific Coast‐wide phenomena, while representing the bathymetric features and submesoscale circulation that affect the transport of nutrients from natural and human sources. Moreover, the model allows simulations at time scales that approach the interannual frequencies of ocean variability. The model simulation is evaluated against a broad suite of observational data throughout the SCB, showing realistic depiction of the mean state and its variability with satellite and in situ measurements of state variables and biogeochemical rates. The simulation reproduces the main structure of the seasonal upwelling front, the mean current patterns, the dispersion of wastewater plumes, as well as their seasonal variability. Furthermore, it reproduces the mean distributions of key biogeochemical and ecosystem properties and their variability. Biogeochemical rates reproduced by the model, such as primary production and nitrification, are also consistent with measured rates. This validation exercise demonstrates the utility of using fine‐scale resolution modeling and local observations to identify, investigate, and communicate uncertainty to stakeholders to support management decisions on local anthropogenic nutrient discharges to coastal zones. Plain Language Summary: We applied and validated an ocean numerical model to investigate the effects of land‐based and atmospheric nutrient loading on coastal eutrophication and its effects on carbon, nitrogen, and oxygen cycles of the Southern California Bight, an upwelling‐dominated marine embayment on the U.S. West Coast. The model is capable of high‐resolution, multiyear hindcast simulations, which enable investigations to disentangle natural variability, climate change, and local human pressures that accelerate land‐based and atmospheric nutrient loads. The model performance assessment illustrates that it faithfully reproduces monitored ocean properties related to algal blooms, oxygen, and water acidity, among others, that can be traced to land‐based and atmospheric inputs of nutrients and carbon from human activities. The model performance assessment helps to constrain uncertainties in predictions to support ongoing conversations on approaches to reduce the effects of climate change, including considerations of management of local nutrient and carbon inputs. Key Points: The model reproduces gradients of physical and biogeochemical properties in the SCB, including seasonal, interannual, and ENSO variability Resolving submesoscale currents increases the vertical flux of nutrients and allows realistic reproduction of wastewater plume circulation Wastewater and riverine inputs are consistent with intensified nutrients, productivity, export, and remineralization nearshore